The Willingness of Dental Medicine Students in Handling Positive HIV Patients - Alya Sahilla Fahri1 , Nurhana Binti Suhaimi1, Balwinjit Kaur Sidhu1 , Yaaliny A/P Krishnamurthi1 , O (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Dental care for HIV positive people plays an important role in increasing quality of life,tolerance and effectiveness of treatment, nutritional intake, and treatment success rates. Therefore, it isimportant to ensure optimal dental care for this group of people, especially since many of them, with or withoutknowledge of their serological status, are now using dental services. Purpose: is to assess the willingnessof dental students to treat HIV positive people. Materials and Methods: A descriptive cross-sectionalsurvey was conducted. In the city of Surabaya, there are around 184,000 HIV positive people. This researchwas conducted in 2019 using a questionnaire designed to obtain information about student demographics,self-assessment of HIV, attitudes toward infection control practices, perceptions of occupational risks, andwillingness to provide care for HIV positive people. Results: The response rate is 76.3 percent. More than77 percent of respondents are in the age group of 19 years to age 25 years. Good knowledge about HIV isonly owned by 35 percent of respondents. While around 7.1 percent, showed significant concern about jobtransmission. Conclusions: From the results of this study, the authors suggest the need for a comprehensiveeducation or motivation program for the next generation of dentists in Indonesia to ensure adequate care forHIV positive people.